2008
DOI: 10.1007/s10886-008-9442-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electrophoretic Protein Profiles from Sheep and Goat Parotid Saliva

Abstract: Saliva provides a medium for short-term adaptation to changes in diet composition, namely, the presence of plant secondary metabolites. Salivary proteins have biological functions that have particular influence on oral homeostasis, taste, and digestive function. Some salivary proteins, such as proline-rich proteins, are present in browsers but absent in grazers. Despite the significance of salivary proteins, their expression patterns in many herbivores are unknown. We investigated the sodium dodecyl sulfate-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 56 publications
5
29
0
Order By: Relevance
“…Distel and Provenza (1991) did not find TBSPs in the saliva sampled from the oral cavity of goats and Lamy et al (2008) did not find TBSPs in sheep and goat parotid saliva. Austin et al (1989) did not identify TBSPs in cattle and the tannin-binding capacity of salivary proteins for tannins did not differ between cows fed high-or low-tannin diets (Makkar and Becker 1998).…”
Section: Introductionmentioning
confidence: 85%
“…Distel and Provenza (1991) did not find TBSPs in the saliva sampled from the oral cavity of goats and Lamy et al (2008) did not find TBSPs in sheep and goat parotid saliva. Austin et al (1989) did not identify TBSPs in cattle and the tannin-binding capacity of salivary proteins for tannins did not differ between cows fed high-or low-tannin diets (Makkar and Becker 1998).…”
Section: Introductionmentioning
confidence: 85%
“…Different ruminant feeding styles (browser vs grazer) were related to differences in salivary proteome. For example goats and sheep differ in the expression level of several parotid salivary proteins, such as one isoform of carbonic anhydrase VI and some isoforms of clusterin precursor, among others (Lamy et al 2008(Lamy et al , 2009.…”
Section: Assessing Diet Composition and Voluntary Food Intake In Montadomentioning
confidence: 99%
“…The affinity to bind tannins has been mostly associated with proline rich proteins (PRPs), which are the most well studied among the TBSPs (Shimada 2006). Lamy et al (2008Lamy et al ( , 2009 were unable to identify PRPs in parotid saliva from sheep and goat breeds, commonly present in Montado. In the case of goats, which usually ingest higher levels of tannins, comparatively to sheep, this may suggest the existence of other defense mechanisms.…”
Section: Assessing Diet Composition and Voluntary Food Intake In Montadomentioning
confidence: 99%
“…In goats, only a few studies have investigated the TBSP. Lamy et al (2008) found major differences in saliva protein within the range of 25-35 kDa and hypothesized their relation with differences on feeding behaviour comparatively to sheep. No PRPs were found either in sheep or in goats maintained on a regular tannin-free diet (Lamy et al 2009).…”
Section: Introductionmentioning
confidence: 94%